Custom-designed metal-free quinoxaline sensitizer for dye-sensitized solar cells based on cobalt redox shuttle. (15th July 2018) - Xu, Liang; Xin, Chenghao; Li, Chen; Wu, Wenjun; Hua, Jianli; Zhu, Weihong
Highlights: The structural modification of the sensitizer is more significant for the cobalt electrolyte. Long alkyl antenna group cause the enhancement of electronic lifetime. The higher PCE was got at lower irradiation. Abstract: Cobalt redox shuttles, as a single electron transfer system, have been attracted widely attention in the area of dye-sensitized solar cells (DSSCs) over the past years. Herein, by means of the expansion of the conjugate system and graft of long alkyl antenna group in organic sensitizer, the intramolecular charge transfer rate and electron recombination inhibition capability are evidently improved. Compared with the iodine electrolyte, the structural modification of the sensitizer is more significant for the cobalt electrolyte, especially the open circuit voltage. As a result, for IQ4 and IQ22, the Jsc and Voc increased from 13.30 mA cm −2 and 810 mV to 15.32 mA cm −2 and 840 mV, respectively. For iodine electrolyte, its open circuit voltage remained essentially unchanged. It proves to be a profitable groundwork for the photovoltaic relationship between cobalt redox couple and the structure of organic sensitizers.